Relasi Makna Sinonimi dalam Album Menari Dengan Bayangan Karya Hindia: Kajian Semantik: The Meaning Relation of Synonymy in Hindia’s Album Menari Dengan Bayangan: Semantic Study - Marwan, Iwan; Masfufah, Farah Anjeliea (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
This research aims to describe the meaning relations of synonymy in the album Menari Dengan Bayangan by Hindia. This research uses descriptive qualitative method. The theory used is semantic meaning relation theory. The data of this research are morphemes, words and phrases contained in 15 songs in the album Menari Dengan Bayangan by Hindia. This research is conducted to reveal how the meaning relations of synonymy that occur in the song album by Hindia. The data collection techniques used are listening techniques and note-taking techniques. The systematic data analysis is in the form of data reduction, data presentation, and conclusion drawing. The results of this study found the existence of synonymy meaning relations contained in 43 data, including; 5 data of synonymy between free morphemes and bound morphemes that have meaning as a form of ownership of pronomina or personal pronouns, 26 data of synonymy between words and words that have meaning as a form of will, hope, action, and feelings, 10 data of synonymy between words and phrases that have meaning as a form of state, difficulty, period, and attitude, and 2 data of synonymy between phrases with phrases that have meaning as a form of action or feeling.